Pengujian Kekerasan dan Struktur Mikro Sambungan Low-Carbon Steel dan Austenitic Stainless Steel - Nugroho Pratomo Ariyanto; Andy Parulian Siregar; Hanifah Widiastuti; Wowo Rossbandrio; Aulia Fajrin; Cahyo Budi Nugroho (Jurnal Teknologi dan Riset Terapan (JATRA), 2022)
High residual stress can occur in stainless steel and carbon steel weld joints due to difference of thermal expansion coefficients. Corrosion-resistant and mechanical properties of weld joint is affected by stainless steel sensitization, resulted by chromium carbide precipitation, and carbon diffusion on heat-affected zone. This study is conducted to investigate post-weld heat treatment effects of stainless steel 316 and AISI 1018 weld joint with 309L filler metal. As the post-weld heat treatment temperature rises between 400 and 700°C, the hardness value decreases. Observed microstructure of heat-affected zone shows dominance of ferrite phase which experiencing grain growth.